Case Report: Regulatory T Cell-Independent Induction of Remission in a Patient With Collagenous Colitis - Honjo, Hajime; Watanabe, Tomohiro; Tomooka, Mizuki; Matsubara, Takuya; Kono, Masashi; Sekai, Ikue; Hara, Akane; Kurimoto, Masayuki; Yoshikawa, Keisuke; Masuta, Yasuhiro; Otsuka, Yasuo; Takada, Ryutaro; et al. (Frontiers in Medicine, 2021)
Collagenous colitis (CC), a prototypical microscopic colitis, is a chronic inflammatory disorder of the colon. The diagnosis of CC depends on the pathological examination. The colonic mucosa of patients with CC is characterized by the presence of a substantially thickened collagen band (>10μm) under the surface epithelium. In addition, intraepithelial and lamina propria lymphocytes are markedly increased in patients with CC. However, the roles played by the lymphocytes accumulating in the colonic mucosa of patients with CC are poorly defined. Recent studies indicate that T cells infiltrating the colonic mucosa of patients with CC are mainly represented by CD4+ T cells, CD8+ T cells, and forkhead box P3 (FOXP3)+ regulatory T cells (Tregs). Given that activation of CD4+/CD8+ T cells and FOXP3+ Tregs usually mediates pro-inflammatory and anti-inflammatory responses, respectively, alterations in the colonic numbers of these adaptive T cells might be related to the resolution of colitis in patients with CC. We determined alterations in the composition of colonic T cells by extensive immunohistochemical (IHC) analyses in a case of CC successfully treated with budesonide and metronidazole. Colonic lamina propria immune cells mainly comprised CD3+ T cells, CD4+ T cells, CD8+ T cells, CD68+ macrophages, and FOXP3+ Tregs, but not CD20+ B cells or myeloperoxidase (MPO)+ granulocytes in the active phase. During remission, the numbers of CD3+ T cells, CD4+ T cells, CD8+ T cells, and CD68+ macrophages did not change significantly in the colonic lamina propria, whereas FOXP3+ Tregs were markedly decreased, suggesting that induction of remission was achieved in a Treg-independent manner. Thus, our study indicates that accumulation of FOXP3+ Tregs in the colonic mucosa of patients with CC might be a counter-regulatory mechanism reflecting persistent inflammation and that induction of remission might be achieved without activation of Tregs.